Eyeing Innocent Souls: The trajectory of Domestic violence and children's education in Botswana: Effects of Domestic Violence on Children's education in Botswana - Mhlauli, Mavis Bashingie (Advances in Social Sciences Research Journal, 2020)
The purpose of this paper is to interrogate the effects of domestic violence among children in Botswana. Domestic violence is a global problem as it affects people from both poor and stable economies. Research has shown that there is a link between domestic violence and child abuse. This link has been shown in and confirmed by various studies conducted in a number of countries including China, South Africa, Colombia, India, Egypt, Philippines and Mexico (Unicef, 2005). Botswana like many countries of the world has a challenge of protecting children from being victims of domestic violence. Most violence in Botswana is reported to occur within intimate relationships which takes the form of emotional, physical and psychological abuse and mostly occurs among women. It has also been observed that domestic violence is common mostly in male dominated cultures which are either patriarchal or patrilineal and often justified by their customs and traditions, and condoned by law (Kanchipuntu and Mwale, 2016). This violence is said to affect children’s lives as it may result in emotional trauma, physical and psychological barriers in schooling and educational experience in general (Lloyd, 2018). Paradoxically, children find themselves entangled in domestic violence with very little knowledge of what steps to take to end the form of abuse they experience. Governments, education systems and schools in particular have a role to play to mitigate the situation that children find themselves in hence the suggested strategies. More research needs to be undertaken to develop ways of dealing with domestic violence in schools which are culturally sensitive..